A 55‐year‐old COVID‐19‐positive man managed with self‐regulation of high‐flow oxygen by high‐velocity nasal insufflation therapy. Issue 5 (21st May 2020) - Ciment, Ari J.; Ciment, Lawrence M.
Abstract: Management of critically ill coronavirus disease 2019 (COVID‐19) patients remains both risky and technically challenging. A 55‐year‐old male COVID‐19‐positive patient with obstructive sleep apnoea (OSA), diabetes, and obesity presented with cough and shortness of breath, escalating to requiring high‐flow oxygen therapy by high‐velocity nasal insufflation. The patient's flow rate and oxygen fraction remained labile throughout much of the hospitalization. This lability required frequent clinician interactions and use of personal protective equipment. The patient was alert and oriented and was instructed on the operation of the high‐flow system, specifically the adjustment of both flow rate and oxygen percentage. The patient was instructed to modify oxygen to maintain an SpO2 (peripheral capillary oxygen saturation) target range, and flow rate to address dyspnoea as well as reduction of flow as tolerated when other staff entered the room. The patient was successfully self‐regulated for 10 days and was discharged on 2 L/min nasal cannula on day 14 of his illness. Abstract : We present a case report on a 55‐year‐old male with obstructive sleep apnoea (OSA), diabetes, and obesity requiring escalation to high‐flow oxygen by high‐velocity nasal insufflation (HVNI; Vapotherm). As this patient required frequent clinician interaction and use of personal protective equipment (PPE) to control flow rate and oxygen fraction due to lability, and the patient was alert, we instructed the patient to modify the oxygen to maintain an SpO2 (peripheral capillary oxygen saturation) target range and flow rate, to address dyspnoea as well as reduction of flow, as tolerated, when other staff entered the room. This was a successful 10‐day self‐regulation of HVNI, wherein on day 14 the patient was discharged.